Preliminary Exploration of the Genetic Diversity and Structure of 107 Amynthas morrisi Specimens - Jing Sun, Jibao Jiang, Juzhen Wu, Yan Dong, Liangliang Zhang, Guihua Zheng, Bo Yao, Jiangping Qiu (Forest Chemicals Review, 2022)
Earthworm plays an important role in soil ecological function, and more and more attentions were paid to the genetic variation of some representative earthworms, but not much for Amynthas species which were presumed mainly originated from China. In this study, based on the mitochondrial COI gene fragment, the genetic diversity, genetic structure, genetic differentiation and variation, and population history dynamics of 107 earthworm specimens of Amynthasmorrisi (Bedard, 1892)) were analyzed. The results showed the 11 haplotypes in 107 samples, including five shared haplotypes and six unique haplotypes. The population had low genetic diversity (HD = 0.745 ± 0.027, π = 0.00800 ± 0.00216) and moderate genetic differentiation (FST= 0.21475, P < 0.001). Eastern hilly plain subregion (VIA) geographical population has the highest genetic diversity and the maximum genetic distance compared to other populations. 78.52% of the genetic variation was from within geographical populations and 21.48% from inter-populations. The divergence time estimation for 11 haplotypes divided into four lineages indicated that the genetic diversification of lineages occurred after Pliocene.